Combined repetitive transcranial magnetic stimulation and functional electrical stimulation cycling to improve lower extremity function following incomplete spinal cord injury: Protocol for a pilot randomized controlled trial - Fereshteh Ghahremani; Siobhan Schabrun; Sue Peters; Laura Brunton; Janelle Unger (PLoS ONE, 2026)
Background Spinal cord injury (SCI) is a neurological condition that affects thousands of individuals globally each year. Among its many consequences, lower extremity impairments, including reduced walking function, balance deficits, and muscle weakness, significantly impact mobility and quality of life. Various rehabilitation approaches aim to restore function, including neuromodulation strategies, such as functional electrical stimulation (FES) cycling and repetitive transcranial magnetic stimulation (rTMS). While both interventions have shown effectiveness in improving lower extremity function following SCI, they have yet to be performed together to determine the combined effectiveness. This pilot trial will evaluate the feasibility and safety of combining rTMS and FES cycling in people with motor incomplete SCI (iSCI) and provide information to determine a sample size for a full randomized controlled trial. Secondary outcomes will explore the effectiveness of the combined intervention on lower extremity function. Methods This is a pilot randomized controlled trial with assessor and participant blinding. Fourteen participants will be randomized to receive either active or sham rTMS prior to FES cycling for a total of 12 sessions over six weeks. Functional outcomes, including gait parameters, muscle strength, and balance tests, will be assessed at baseline, midpoint, post-intervention, and two weeks following treatment cessation and will be assessed both within and between groups to explore trends in efficacy. Feasibility and safety data will be analyzed descriptively. Implications This study aims to establish a protocol and sample size for running a full randomized controlled trial on the effectiveness of combining rTMS and FES cycling for lower extremity rehabilitation in iSCI. The protocol is registered with ClinicalTrials.gov (ID: NCT05975606 ).